Balancing affordability and comfort: exploring residential factors in thermal comfort assessment of urban low-cost flats in Kuala Lumpur - Muhamad, Siti Nurfahirah; How, Vivien; Mohd Shabr, Nur Shabrina Azreen; Karuppiah, Karmegam; Lim, Fang Lee; Md Akim, Abdah (Universiti Putra Malaysia Press, 2024)
Introduction: Most affordable residential buildings in Kuala Lumpur are primarily multi-story structures designed to maximize space utilization. The objective of our study is to evaluate the thermal comfort and identify the factors that affect the levels of heat exposure in these buildings during the Southwest monsoon season. Materials and methods: We employed multistage sampling to recruit 55 units from three affordable apartments (low-cost flat) in Kuala Lumpur. Wet-bulb globe temperature (WBGT) was used to monitor heat parameters, categorized thermal comfort using the Universal Thermal Climate Index (UTCI), and acquire residential factors through the characterization of sampled areas. Results: All of the flats we examined had ambient and radiant temperatures that were higher than the recommended ranges, leading to “moderate” to “strong” UTCI thermal stress. The age of the building, the density of the building, and the floor level all had a statistically significant impact on UTCI heat exposure (p<0.05). Conclusion: Therefore, it is essential to employ cooling systems in order to improve indoor air circulation, reduce temperatures, and minimize the dangers associated with high temperatures, especially during periods of intense heat.